MELAHIRKAN GENERASI QUR'ANI: PEMAKNAAN QUR'ANI DALAM MEMBANGUN PERADABAN ISLAM - Sofyan Siddiq Fuad Baswedan; Emha Hasan Nashrulloh; Irsyad (CV. Adiba Aisha Amira, 2025)
This study examines the importance of educating a generation based on the Qur'an as a foundation for building a sustainable Islamic civilization. The Qur'an, as the main source of values and ethics for Muslims, serves as a guideline for shaping individual character and contributing to society. This study uses a qualitative approach, focusing on literature review and comparative analysis of classical and contemporary interpretations of the Qur'an. The research findings indicate that instilling Qur'anic values through education is essential for building a just and prosperous society. Proper interpretation and internalization of these values enable Muslims to face contemporary challenges and contribute to building a resilient Islamic civilization